ANALISIS MANAJEMEN RISIKO OPERASIONAL PADA UMKM DEPOT AIR MINUM ISI ULANG "SAMSUL WATER" PINANG BARIS - Gusti maia firanti noor; Siti Maisarah; Luviah Permadhani; Azizah Azzahra; Ayunda Fatmasari (Journal of Innovative and Creativity (Joecy), 2026)
OBJECTIVE – This study aims to identify the various operational risks faced by the Samsul Water Refill Drinking Water Depot MSME (Micro, Small, and Medium Enterprise), analyze the likelihood and impact of each identified risk, and determine the priority level of risks based on assesment results using the risk register method. FOCUS – This study focuses on analyzing operational risk management in the business processes of the Samsul Water Drinking Water Depot MSME. The analysis is conducted by identifying risks in each operational activity and assesing the level of risk based on likelihood and impact to determine risk handling priorities. METHOD – This study employs a descriptive qualitative approach. Data were collected through in-depth interviews and documentation of daily operational activities. The collected data were analyzed by identifying risk patterns and drawing conclusions based on thematic interpretation. FINDINGS – The findings identified six major operational risks: water storage tank damage, filter blockage, operational vehicle problems, damaged water gallons, employee work delays, and delays in the supply of raw water from mountain sprimgs. The recommended mitigation strategies include regular maintenance and inspections of equipment, implementation of maintenace Standard Operating Procedures (SOP), and enhanced operational supervision to support business sustainability